Capitalism and Socialism: A Review of Kornai's Dynamism, Rivalry, and the Surplus Economy - Xu, Chenggang (Journal of Economic Literature, 2017)
Understanding the nature of capitalism has been a central theme of economics. The collapse of the Eastern Bloc and the global financial crisis spurred the reemergence of the political economy as a new frontier and the revival of interest in the nature of capitalism. János Kornai's book Dynamism, Rivalry, and the Surplus Economy: Two Essays on the Nature of Capitalism fills an important intellectual gap in understanding the dynamic nature of capitalism by comparing it with its mirror image, socialism. To further develop the themes contained in the book, serious challenges are posed theoretically and empirically, as well as in subjects, such as hybrid capitalism. (JEL L32, P12, P14, P16, P26, P31)